Legal framework for protecting bank customers against personal data leakage in the digital era: A study of Indonesian regulations - Lazuardy, Moch Syahren; Rachmawati, Maya; Marlina, Tina; Umar, Jaenudin (International Journal Labs, 2024)
In the digital era, the protection of personal data is crucial due to the growing privacy of individuals and the potential for security risks, including cyber threats. This research aims to provide a deeper understanding of the Indonesian legal regulations in safeguarding personal data and how this can affect public trust in financial institutions, especially banks, in maintaining the security of their customers' data from data leaks. The author uses a normative juridical research method by taking an approach that is carried out based on the main legal materials by examining the laws and regulations related to this research. The focus of this research is legal protection for bank customers in protecting personal data leakage in the era of rapid technology. The research contribution lies in exploring and analyzing the effectiveness of Indonesian law regulations in protecting the personal data, and how these measures influence public confidence in the banking sector.